Bio‐Inspired Conformable and Helical Soft Fabric Gripper with Variable Stiffness and Touch Sensing. Issue 12 (5th November 2020) - Hoang, Trung Thien; Phan, Phuoc Thien; Thai, Mai Thanh; Lovell, Nigel H.; Do, Thanh Nho
Abstract: There are many instances in nature where continuum, helical manipulators are used to efficiently grasp different objects with various shapes and sizes. Inspired by nature, this paper introduces a continuum, flat, scalable, helical soft‐fabric robotic gripper that is thin and lightweight with stiffness tunability and sensory feedback. The gripper is fabricated by a facile method of simple insertion using a computerized technique from apparel engineering and controlled by a miniature hydraulic source to grasp different objects at different scales and weights. It uses a thermally activated variable stiffness structure (VSS) for high load capacity that can complete a softening‐stiffening cycle within 24 s, which is among the fastest results reported so far. In addition, a highly stretchable liquid metal‐based soft sensor with an enhanced sensing sensitivity (15 times more sensitive compared to conventional designs) is embedded into the gripper to provide real‐time touch sensing. The gripper successfully grasped various objects of different geometries and weights (up to 220 times of its mass) and retrieved them from confined hollow spaces. Its excellent performance and versatility make it an ideal candidate for various domains, including industry, exploration, rescue, and other applications in confined and hazardous environments such as gas/oil or drainage sectors. Abstract : A continuum, flat, and scalable helical soft hydraulic fabric gripper with tunable stiffness and sensory feedback is presented. It is fabricated by a facile method of simple insertion and computerized technique of apparel engineering. The soft gripper is demonstrated for gripping various objects at different geometries and weights, as well as retrieving grasped objects from confined spaces.